2015
DOI: 10.1017/s0950268815001314
|View full text |Cite
|
Sign up to set email alerts
|

Evolving epidemiology of Nipah virus infection in Bangladesh: evidence from outbreaks during 2010–2011

Abstract: SUMMARYDrinking raw date palm sap is the primary route of Nipah virus (NiV) transmission from bats to people in Bangladesh; subsequent person-to-person transmission is common. During December 2010 to March 2011, we investigated NiV epidemiology by interviewing cases using structured questionnaires, in-depth interviews, and group discussions to collect clinical and exposure histories. We conducted a case-control study to identify risk factors for transmission. We identified 43 cases; 23 were laboratory-confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Person-to-person transmission is an important pathway for NiV-BD infection of people [ 2 ], while for NiV-MY most patients acquired their infection from domestic pigs [ 3 , 4 ]. It has been suggested that a greater prevalence and severity of respiratory disease signs in patients infected with NiV-BD may facilitate person-to-person transmission by this strain [ 2 , 5 ], and exposure to respiratory secretions from patients is reported to be a major risk factor for onward NiV-BD transmission [ 6 , 7 ]. However, NiV-MY has also been isolated from respiratory secretions [ 8 ], and so the factors responsible for different strain attack rates remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Person-to-person transmission is an important pathway for NiV-BD infection of people [ 2 ], while for NiV-MY most patients acquired their infection from domestic pigs [ 3 , 4 ]. It has been suggested that a greater prevalence and severity of respiratory disease signs in patients infected with NiV-BD may facilitate person-to-person transmission by this strain [ 2 , 5 ], and exposure to respiratory secretions from patients is reported to be a major risk factor for onward NiV-BD transmission [ 6 , 7 ]. However, NiV-MY has also been isolated from respiratory secretions [ 8 ], and so the factors responsible for different strain attack rates remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, variable flying fox (Pteropus hypomelanus) and large flying fox (P. vampyrus) were found as natural reservoir hosts for Nipah virus (Chua et al, 2002a;Chua et al, 2002b). Nipah virus associated disease was also reported from human in Bangladesh (Sazzad et al, 2013;Chakraborty et al, 2016). Nipah virus outbreak in Bangladesh was very similar to Malaysian outbreak in several aspects such as fever, central nervous system signs, delayed recognition and a high case fatality rate.…”
Section: Henipavirus (Hendra and Nipah Virus)mentioning
confidence: 99%
“…P. medius individuals feed on wild and cultivated fruits and flowers, and visit date palm trees during sap collection to feed on the sap stream (Khan et al, 2010). Drinking date palm sap contaminated with urine or saliva of NiV-infected bats has been identified as a major route of zoonotic transmission of NiV (Chakraborty et al, 2016;Luby & Gurley, 2015). However, humanto-human NiV transmissions represent 33% of known Nipah virus human cases from Bangladesh between 2001 and 2014 (Nikolay et al, 2019).…”
mentioning
confidence: 99%